Peran Teknologi Digital Dalam Mendukung Daya Saing Anak - Herwin Herwin; Vina Meliana (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2019)
Community Service is one of the implementations of the Tri Dharma of Higher Education activities conducted by Kalbis Institute of Technology and Business lecturers. One form of community service that will be carried out is to prepare the role of parents in responding to digital technology so that it can be utilized as competitiveness for their children. The implementation of PKM activities went smoothly, the benefits gained by PKK RT 026 RW 03, Kebon Manggis Sub-District, Matraman District, East Jakarta after attending the training are: (1) PKK communities can be motivated to develop themselves, can recognize learning methods, by using appropriate learning media; (2) PKK communities know the development of digital technology including the Internet of Thing, Artificial Intelligent and Big Data. (3) PKK communities know the impact of competition in the globalization era which is very influential on children's learning and playing patterns, potential by recognizing the validity of sources. (4) PKK communities can screen information that is useful for families, especially children. For further PKM activities, training can be given on motivating (directing) school-age children and technology-based learning. Keywords: Internet of Thing, Artificial Intelligent, Big Data